PEMBUATAN NANOPARTIKEL PERAK (AgNP) DENGAN ANTIBAKTERI BIOREDUKTOR EKSTRAK AMPAS JERUK NIPIS (CITRUS AURANTIFOLIA) - Robinson Manalu; Efie Indrianti; Muhtar, Diki (Jurnal Teknologika, 2024)
Silver nanoparticles have been made with several different methods and conditions including chemical reduction methods, photochemistry, sonochemistry, ultrasonic radiation,. The synthesis of silver nanoparticles (AgNP) in this study used a chemical reduction method because this method is easy to do, simple, environmentally friendly and produces quite good silver nanoparticles (AgNP). In the process of synthesizing silver nanoparticles (AgNP), a bioreductant of lime peel extract (Citrus aurantifolia) was used as a reducing agent and polyethylene glycol (PEG) 6000 as a stabilizer. In principle, silver nanoparticles (AgNP) by chemical reduction method, silver metal ions are reduced by a bioreductant of lime peel extract (Citrus aurantifolia) and with the addition of polyethylene glycol (PEG) 6000 to stabilize silver nanoparticles (AgNP). The silver nanoparticle (AgNP) solution formed was then analyzed for its characteristics using UV-Vis spectrophotometer and Particle Size Analyzer (PSA). The result of UV-Vis spectrophotometer analysis showed that the most stable silver nanoparticles (AgNP) were those synthesized using a 3 mL bioreductant, pH 11 and the ratio of AgNO3 : PEG-6000 (1 : 1) resulted in an absorbance peak at a wavelength of 420 nm. Characterization using Particle Size Analyzer (PSA) showed the smallest silver nanoparticle size (AgNP) was 40 nm with an average size of 352 nm, median of 70 nm, mode of 67 nm and volume of silver nanoparticle size (AgNP) of 73.11. %.